Enhanced Increases in Cytosolic Ca2+ in ADP-Stimulated Platelets from Patients with Delta-Storage Pool Deficiency – A Possible Indicator of Interactions between Granule-Bound ADP and the Membrane ADP Receptor - Lages, Bruce; Weiss, Harvey J (Thrombosis and Haemostasis, 1997)
The possible involvement of secreted platelet substances in agonist- induced [Ca2+]i increases was investigated by comparing these increases in aspirin-treated, fura-2-loaded normal platelets and platelets from patients with storage pool deficiencies (SPD). In the presence and absence of extracellular calcium, the [Ca2+]i response induced by 10 µM ADP, but not those induced by 0.1 unit/ml thrombin, 3.3 µM U46619, or 20 µM serotonin, was significantly greater in SPD platelets than in normal platelets, and was increased to the greatest extent in SPD patients with Hermansky-Pudlak syndrome (HPS), in whom the dense granule deficiencies are the most severe. Pre-incubation of SPD-HPS and normal platelets with 0.005-5 µM ADP produced a dose-dependent inhibition of the [Ca2+]i response induced by 10 µMADP, but did not alter the [Ca2+]i increases induced by thrombin or U46619. Within a limited range of ADP concentrations, the dose-inhibition curve of the [Ca2+]i response to 10 µM ADP was significantly shifted to the right in SPD-HPS platelets, indicating that pre-incubation with greater amounts of ADP were required to achieve the same extent of inhibition as in normal platelets. These results are consistent with a hypothesis that the smaller ADP-induced [Ca2+]i increases seen in normal platelets may result from prior interactions of dense granule ADP, released via leakage or low levels of activation, with membrane ADP receptors, causing receptor desensitization. Addition of apyrase to platelet-rich plasma prior to fura-2 loading increased the ADP-induced [Ca2+]i response in both normal and SPD-HPS platelets, suggesting that some release of ADP derived from both dense granule and non-granular sources occurs during in vitro fura-2 loading and platelet washing procedures. However, this [Ca2+]i response was also greater in SPD-HPS platelets when blood was collected with minimal manipulation directly into anticoagulant containing apyrase, raising the possibility that release of dense granule ADP resulting in receptor desensitization may also occur in vivo. Thus, in addition to enhancing platelet activation, dense granule ADP could also act to limit the ADP-mediated reactivity of platelets exposed in vivo to low levels of stimulation.